The Effect of Breadfruit Leaf Flour (Artocarpus altilis) on Number of Blood Cells And Correlation Between Cholesterol Blood and Meat of Tegal Ducks 10 Weeks Age - Tugiyanti, Elly; Susanti, Emmy (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2017)
The purpose of this research was to know the effect of breadfruit leaves flour in feed to blood profile and correlation between cholesterol, HDL and LDL of blood with meat cholesterol of maleTegal duck of 10 weeks old. The material used was Day Old Duck of male Tegal duck Â as much as 120 heads with experimental research methods and Completely Randomized Design (CRD). There were 6 treatments: feed without breadfruit leaf powder, feed + breadfruit flour 3% / kg feed, feed + breadfruit flour 6% / kg feed, feed + breadfruit flour 9% / kg feed, feed + flour breadfruit 12% / kg feed, and feed + breadfruit flour 15% / kg feed. Each treatment was repeated 5 times and each replication consisted of 4 ducks. The variables observed were the number of red blood cells, white blood cells, HDL, LDL, blood triglycerides, correlation between cholesterol, HDL and LDL blood with meat cholesterol of male Tegal duck of 10 weeks old. Â The result of the analysis showed that the supplementation of breadfruit leaves has significant effect (P <0,05) on the number of red blood cells, white blood cells, HDL, and blood triglyceride. There is a positive correlation between blood cholesterol with duck meat cholesterol which given breadfruit leaf powder. This research can be concluded that the supplementation of breadfruit leaf powder (Artocarpus altilis) can increase the number of red blood cells, white blood cells, blood HDL level but lowers blood cholesterol and triglyceride blood of male Tegal duck of 10 weeks old. Cholesterol meat is affected by blood cholesterol with regression coefficient of 0.780941, influenced by LDL (r = 0.407849), but negatively affected by HDL (r = -0.47022).